PERENCANAAN DALAM PERSPEKTIF MANAJEMEN ISLAM (Telaah Al-Qur’an Surat Al-Anfâl/ 8 Ayat 60) - AKMANSYAH, MUHAMMAD (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2015)
Abstract Islam has already given the principles of management in the Holy Qur’an. Management that is considered to be one of the most important subjects of modern times is also derived from the knowledge that the Holy Qur’an has given us. Many of its principles and theories that are made in sixteenth or seventeenth century are derived from the knowledge that The Holy Qur’an has given us centuries ago. There are some verses in the holy Qur’an on management; these verses should be studied for explaining the managerial view of the holy Quran. One of that principles is planning. The planning is the function of management that involves setting objectives and determining a course of action for achieving those objectives. The planning is a process begins with environmental scanning which simply means that planners must be aware of the critical contingencies facing their organization in terms of economic conditions, their competitors, and their customers. Planners must then attempt to forecast future conditions. These forecasts form the basis for planning. This article will discuss about the planning, as one the function of management, according to Surat al-Anfâl/8 verse 60. Allah said, “Against them make ready your strength to the utmost of your power including steeds of war to strike terror into (the hearts of) the enemies of Allah and your enemies and others besides whom ye may not know but whom Allah doth know. Whatever ye shall spend in the cause of Allah shall be repaid unto you and ye shall not be treated unjustly.”